Percutaneus Transluminal Angioplasty Using Carbon Dioxide Contrast in Chronic Limb Threatening Ischemia patient with Renal Failure - Saga Malela Aria Sabara; Suko Adiarto (Majalah Kardiologi Indonesia)
Background: